Effect of Pre-Fermentative Maceration and Fining Agents on Protein Stability, Macromolecular, and Phenolic Composition of Albariño White Wines: Comparative Efficiency of Chitosan, k-Carrageenan and Bentonite as Heat Stabilisers - Inma Arenas; Miguel Ribeiro; Luís Filipe-Ribeiro; Rafael Vilamarim; Elisa Costa; João Siopa; Fernanda Cosme; Fernando M. Nunes (Foods, 2021)
In this work, the effect of pre-fermentative skin maceration (PFSM) on the chemical composition of the macromolecular fraction, polysaccharides and proteins, phenolic compounds, chromatic characteristics, and protein stability of Albariño monovarietal white wines was studied. PFSM increased the extraction of phenolic compounds and polysaccharides and reduced the extraction of pathogenesis-related proteins (PRPs). PFSM wine showed significantly higher protein instability. Sodium and calcium bentonites were used for protein stabilisation of wines obtained with PFSM (+PFSM) and without PFSM (−PFSM), and their efficiencies compared to fungal chitosan (FCH) and k-carrageenan. k-Carrageenan reduced the content of PRPs and the protein instability in both wines, and it was more efficient than sodium and calcium bentonites. FCH was unable to heat stabilise both wines, and PRPs levels remained unaltered. On the other hand, FCH decreased the levels of wine polysaccharides by 60%. Sodium and calcium bentonite also decreased the levels of wine polysaccharides although to a lower extent (16% to 59%). k-Carrageenan did not affect the wine polysaccharide levels. Overall, k-carrageenan is suitable for white wine protein stabilisation, having a more desirable impact on the wine macromolecular fraction than the other fining agents, reducing the levels of the wine PRPs without impacting polysaccharide composition.